Synthesis, Characterization and Thermogravimetric Study of Some Metal Complexes of Selenazone Ligand Nanoparticles Analogue of Dithizone - Zuhair Ali Abdulnabi; Faris Abdulridhah Jassim Al-doghachi; Hassan Thamir Abdulsahib (Universitas Gadjah Mada, 2021)
A new method for preparing 1,5-diphenylselenocarbazone (selenazone) nanoparticles and their complexes with Pb2+, Cd2+, Co2+, and Ni2+ has been performed using hot methanol solvent. The ligand and its complexes were characterized using FT-IR, UV-Vis, 1H-NMR, 13C-NMR, X-ray powder diffraction (XRD), EI-mass spectrometry, scanning electron microscopy (SEM), HG and flame-atomic absorption spectrophotometer, thermal analysis (TG/DTA), and molar conductance measurements. The molar conductance measurements in all complexes were recorded low values in DMSO, indicating that all the metal complexes were non-electrolytes except the nickel complex that possessed an electrolytic nature. Kinetic and thermodynamic parameters of complexes (A, E, ∆H, ∆S, and ∆G) have been computed using three kinetic models of Coast-Redfern, Broido, and Horowitz-Metzger, that illustrated the decomposition reactions in all steps were nonspontaneous. Thermogravimetric analyses (TG/DTA) were consistent with the atomic spectroscopy data proving that the geometry shape of all the complexes was octahedral.